Safety and Efficacy of Feed Additives in Animal Production - Gresakova, Lubomira; Sabia, Emilio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on animal nutrition strategies using various feed additives to enhance nutrient digestibility and utilization, modulate the antioxidant capacity, mineral status, immunity, and gut and/or rumen microbiota in livestock. This results in improvements in their growth, performance and production parameters, as well as the quality of animal products.